Study of Leading Commodities in Capture Fisheries Sector in the City of Tidore Islands - Marsaoly, Sardi; Iksan, Kusdi Hi.; Karman, Amirul (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
The aim of the research is to examine and determine leading commodities (comparative and competitive) of capture fisheries in the city of Tidore Islands. Using descriptive survey methods. The data used consists of primary data and secondary data. The results of the research, the city of Tidore Islands has 6 comparatively leading commodities for capture fisheries based on production volume, namely Sardine (Sardinella sp), Garfish (Tylosurus crocodiles), Skip Jack Tuna (Katsuwonus pelamis), Mackarel Tuna (Euthynus sp), Mackarel Scad (Decapterus sp), and Barred Garfish (Hemiramphus sp), and 7 leading fish commodities based on production value namely Sardine (Sardinella sp), Garfish (Tylosurus crocodiles), Skip Jack Tuna (Katsuwonus pelamis), Mackarel Tuna (Euthynus sp), Mackarel Scad (Decapterus sp), Rainbow Runner (Elagatis bipinnulata) and white Snapper (Lates carcarifer). The city of Tidore Islands have 14 leading competitives fish commodities based on production volume namely: Skip Jack Tuna (Katsuwonus pelamis), Mackarel Tuna (Euthynus sp), Barred Spanish mackerel (Scomberomorus sp), Rainbow Runner (Elagatis bipinnulata), Barred Garfish (Hemiramphus sp), Yellowtail (Caesio sp), Grouper (Epinephelus sp), Garfish (Tylosurus crocodiles), Trevally (Caranx sp), Sword fish (Trichiurus lepturus), white snapper (Lates carcarifer), pomfret (Collosoma macropomum), mullet (Valamugil sehali), and Red Snapper (Lutjanus campechanus). Meanwhile based on production value there are 15 fish commodities namely : Skip Jack Tuna (Katsuwonus pelamis), Mackarel Tuna (Euthynus sp), Barred Spanish mackerel (Scomberomorus sp), Rainbow Runner (Elagatis bipinnulata), Barred Garfish (Hemiramphus sp), Sardine (Sardinella sp), Sword Fish (Trichiurus lepturus)...